Homogeneous spaces in Hartree-Fock-Bogoliubov theory - Alvarado, Claudia Damaris (2024)
We study the action of Bogoliubov transformations on admissible generalized one-particle density matrices arising in Hartree-Fock-Bogoliubov theory. We show that the orbits of this action are reductive homogeneous spaces, and we give several equivalences that characterize when they are embedded submanifolds of natural ambient spaces. We use Lie theoretic arguments to prove that these orbits admit an invariant symplectic form. If, in addition, the operators in the orbits have finite spectrum, then we obtain that the orbits are actually Kahler homogeneous spaces.